SENSEMAKING PROCESS IN ORGANIZATIONAL COMMUNICATION: A QUALITATIVE STUDY OF COMMUNITY-BASED ORGANIZATIONS - Harahap, Mhd. Harvinsyah Rozi; Ritonga, Hasnun Jauhari; Tanjung, Ahmad Sujai (Journal Analytica Islamica, 2026)
The development of digital ecosystems and increasing community participation in community-based organizations have given rise to communication complexities that have the potential to create ambiguity of meaning. In this context, the sensemaking process is crucial for understanding how organizational members construct shared understanding and guide collective action. This study aims to analyze the sensemaking process in organizational communication within community-based organizations in the digital era. The study employed a qualitative approach with an interpretive case study design. Data were collected through in-depth interviews with 12 key informants, four months of participant observation, and analysis of internal communication documents and the organization's social media. The analysis was conducted thematically, referring to the stages of enactment, selection, and retention in sensemaking theory. The results indicate that information ambiguity, particularly that originating from digital communication, is a key trigger for the collective meaning-making process. Sensemaking occurs cyclically, influenced by community value framing, relational dynamics, and the mediation of communication technology. These findings expand the application of sensemaking theory by emphasizing the relational and digital dimensions within community-based organizations. Practically, this study emphasizes the importance of digital communication literacy and dialogic leadership in maintaining organizational cohesion and accountability. Future research is recommended to develop comparative and longitudinal studies to deepen understanding of the dynamics of sensemaking across communities.